Treatment strategy for severe implosion injuries of the lateral chest wall Versorgungsstrategie bei schweren Implosionsverletzungen der lateralen Thoraxwand - Schulz-Drost, Stefan; Spering, Christopher (Die Unfallchirurgie, 2024)
In the majority of cases implosion injuries to the thoracic wall are caused by blunt, massive force acting on the thorax. Basically, different regions and directions of the acting energy have to be taken into account. In common usage, the term implosion injury has become established, especially for the sequelae of lateral energy impact. Particular attention should be paid to the stability of the shoulder girdle, the underlying hemithorax and its intrathoracic organs.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Blunt injuries; Chest wall instability; Clavicle fracture; Rib fractures; Shoulder girdle